Dissociation and Wholeness in Patrick White's Fiction - Steven, Laurence, 1953- (Book collections on Project MUSE., 2006)
Patrick White is a man divided: one part of him strives for permanence, surety, the ideal, while knowing the contingent, temporal realm he inhabits must inevitably undermine such striving. The desire, and the knowledge of its futility, leads him into a misanthropic devaluation of human creative possibility and, complementarily, into the arbitrary use of imposed symbolic resolutions directed to an elect who can ""see"". It has been this part of White, largely, that criticism has been industrious in explicating, if not in quite the terms I have used above. But there is another part of White whic.